1994
DOI: 10.1161/01.cir.89.3.1051
|View full text |Cite
|
Sign up to set email alerts
|

Significance of arrhythmias during the first 24 hours of acute myocardial infarction treated with alteplase and effect of early administration of a beta-blocker or a bradycardiac agent on their incidence.

Abstract: BACKGROUND Although early intravenous beta-blocker therapy during acute myocardial infarction (AMI) reduces the incidence of fatal arrhythmias in patients not treated with thrombolytic agents, its antiarrhythmic effect in thrombolysed patients remains controversial. We investigated prospectively the arrhythmia incidence in 244 patients with AMI receiving alteplase and a double-blind randomized adjunctive therapy with intravenous atenolol, alinidine, or placebo. Moreover, the characteristics and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…10 Intravenous β-blocker with thrombolytic therapy did not reduce the incidence of ventricular or supraventricular premature beats, unsustained VT, sustained VT, or Vf. 21 Overall, β-blocker therapy in the acute phase of AMI seems to have little effect on the occurrence of arrhythmias in the thrombolytic era, and our results were consistent with that.…”
supporting
confidence: 90%
“…10 Intravenous β-blocker with thrombolytic therapy did not reduce the incidence of ventricular or supraventricular premature beats, unsustained VT, sustained VT, or Vf. 21 Overall, β-blocker therapy in the acute phase of AMI seems to have little effect on the occurrence of arrhythmias in the thrombolytic era, and our results were consistent with that.…”
supporting
confidence: 90%
“…[10][11][12] However, it is not completely clear whether VT is a marker of inadequate myocardial perfusion after thrombolysis; 13 therefore, a more aggressive attitude has been recommended in these patients based on their high mortality rate. This high mortality rate is partially due to known data: these patients have ventricular function failure more frequently, and VT is a marker of extensive AMI as it has a higher CPK peak.…”
Section: Discussion Sustained Ventricular Tachycardia As a Marker Of mentioning
confidence: 99%
“…[595][596][597][598][599][600][601][602] None of the papers reviewed showed that ␤-blockers caused irreversible harm when given early in the development of suspected ACS. One study showed a statistically significant reduction in 6-week mortality in a subgroup of low-risk (ie, Killip Class I) patients (LOE 1).…”
Section: Acs-023amentioning
confidence: 99%